The best American magazine writing 2017 - Holt, Sid (Columbia University Press, 2017)
Features articles that were judged finalists and winners in the National Magazine Awards, presenting works from leading journalists on such topics as reparations, Internet sexual harassment, the public humiliation complex, and the college rape crisis.